The Interleukin-23 / Interleukin-17 axis in intestinal inflammation. - Maloy, K (2008)
Although the precise aetiology of inflammatory bowel disease (IBD) remains unclear, recent discoveries have led to an improved understanding of disease pathogenesis. Whilst these findings have underscored the central role of innate and adaptive immune responses in intestinal inflammation, they have also precipitated a paradigm shift in the key cytokine pathways that drive disease. The prevailing dogma that IBD was mediated by interleukin (IL)-12-driven T-helper (Th)1 CD4 T cell responses towards the bacterial flora has been largely dispelled by findings that the closely related cytokine IL-23 appears to be the key mediator of intestinal inflammation. IL-23 is associated with a novel subset of IL-17-secreting CD4 T cells termed Th17 cells and rodent studies have implicated the IL-23/IL-17 axis in autoimmune inflammation. Genome-wide association studies in IBD patients have confirmed the predominant role of the IL-23 pathway, indicating that this could represent an important future therapeutic target.